2013
DOI: 10.2174/15734013113099990001
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Beverage with Soy Isoflavone Consumption for Breast Cancer Prevention: A Case-control Study

Abstract: The purpose of this study is to evaluate how beverages containing Lactobacillus casei Shirota (BLS) and soy isoflavone consumption since adolescence affected the incidence of breast cancer. In a population-based case-control study, three hundred and six cases with breast cancer and 662 controls aged 40 to 55 were matched for age and residential area and included in the analyses. Diet, lifestyle and other breast cancer risk factors were investigated using the self-administered questionnaire and interview. Odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…The therapeutic effects resulted from probiotic ingestion are well documented and evident against inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), lactose intolerance, hypercholesterolaemia, immune disorders and cancers amongst others [2,3]. Notwithstanding the numerous findings on the beneficial effects of probiotics, their stability remains a major concern.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects resulted from probiotic ingestion are well documented and evident against inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), lactose intolerance, hypercholesterolaemia, immune disorders and cancers amongst others [2,3]. Notwithstanding the numerous findings on the beneficial effects of probiotics, their stability remains a major concern.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the phylogenetic Lactobacillus casei group has been widely used in commercial, fermented products, the classical example of which is the trademarked Yakult drink, which is fermented by Lactobacillus casei Shirota (Matsumoto et al, 2006;Fujimoto et al, 2008). Lactobacillus casei Shirota has been extensively studied in human clinical trials and showed a wide range of positive effects, including modifying composition and metabolic activity of the gut flora (Spanhaak et al, 1998), improving defecation frequency in suboptimal health subjects (Matsumoto et al, 2006), reducing fever caused by Norovirus gastroenteritis in elderly (Nagata et al, 2011), modulating immune responses in allergic rhinitis (Ivory et al, 2008) and enhancing natural killer cell activity (Toi et al, 2013). Additionally, various strains of probiotics have been commercially developed as nutraceutical supplements (Folign e et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, probiotics may modulate metabolism in the gut so that levels of toxigenic or carcinogenic metabolites become reduced (De Preter et al 2011). Both these mechanisms have been shown with L. casei Shirota and may underlie positive results reported from studies investigating colorectal cancer (Ishikawa et al 2005), breast cancer (Toi et al 2013) and superficial bladder cancer (Ohashi et al 2002).…”
Section: An Overview Of Probiotic Researchmentioning
confidence: 98%